Synthesis of carbon nanostructures from waste materials - Danial, Wan Hazman (Springer, 2024)
Carbon nanostructures have received a tremendous interest by the scientific communities owing to their outstanding properties and unique flexible architectures. Various methods including green nanotechnologies have been developed to address numerous issues and encompass a manufacturing strategy for the conversion of waste materials into carbon nanostructures. This chapter presents an overview of the synthesis of carbon nanostructures such as activated carbon nanoparticles, fullerenes, graphene-based materials, carbon dots, carbon nanotubes, and aerogel from various solid and liquid waste materials. A brief discussion on techniques and valorization of a myriad range of green precursors is also presented. The potential use of waste materials as precursors is not only appealing, affordable, and easily accessible but also provides an avenue or alternatives of waste treatment and recycling effort toward the production of high value-added carbon nanomaterials.